Pengaruh Service Quality terhadap Customer Satisfaction Pada PT. Bank Jateng KCP Cepu - Zariahwati Ajining Pambudi (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2018)
This research has a purpose to know the implementation of Service Quality, to know the Customer Satisfaction at PT. Bank Jateng KCP Cepu. In this study population consists of 1.000 customer satisfaction with a sample of 286 using Incidental sampling technique. Data were taken by questionnaire, observation and documentation. The analysis was processed with SPSS program version 22.0 using simple linear regression with test of hypothesis test of determination and t test. The result of research shows that the result of Simple Linear Regression Test is Y = 9,311 + 0,763 X, constant of 9,311 means if variable of Service Quality is still value then Customer Satisfaction is 0,763 so there is influence between Service Quality to Customer Satisfaction. The result of Coefficient of Determination ( ) is known 0,400 means 40% Service Quality is influenced by Customer Satisfaction, while the rest 60% Service Quality is influenced by other variables not examined in this research. Then, the result of t test obtained value is 13,765 while   equal to 1,9683. This means that the value of    >  (13,765>1,9683) so it can be concluded that Ho is rejected and Ha accepted, meaning there is influence the Service Quality to Customer Satisfaction at              PT. Bank Jateng KCP Cepu.